2023
DOI: 10.2355/isijinternational.isijint-2022-274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molten Steel Composition on Inclusion Modification by Calcium Treatment in Al-Killed Tinplate Steel

Abstract: The effects of oxygen, magnesium, and sulfur content in Al-killed tinplate steel on the "liquid zone" of inclusion modification by calcium treatment were clarified through industrial experiments and thermodynamic calculation, and the characteristics of inclusions modification were studied. The results show that the inclusions in molten steel before calcium treatment are mainly Al 2 O 3 inclusions.The inclusions in molten steel are CaO•Al 2 O 3 after calcium treatment with a holding time of 10min, while the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The range of the error bars for the "experiment"-axis corresponds to the results shown in Table 3; for the "simulation"-axis, the range of the error bars corresponds to the change in thickness as the magnitudes of the contact thermal resistances are changed. Since the model matches the experimental conditions of the immersion of the cored wires, it is expected that simulations extrapolating to industrial processing conditions would allow for producing guidelines for optimization of the cored wire injection process, as a complement to established approaches that combine industrial trials with thermodynamic analyses [44][45][46][47][48][49][50][51][52][53][54][55]. lation"-axis, the range of the error bars corresponds to the change in thickness as the magnitudes of the contact thermal resistances are changed.…”
Section: Comparison Of Experimental Results and Numerical Simulationsmentioning
confidence: 99%
“…The range of the error bars for the "experiment"-axis corresponds to the results shown in Table 3; for the "simulation"-axis, the range of the error bars corresponds to the change in thickness as the magnitudes of the contact thermal resistances are changed. Since the model matches the experimental conditions of the immersion of the cored wires, it is expected that simulations extrapolating to industrial processing conditions would allow for producing guidelines for optimization of the cored wire injection process, as a complement to established approaches that combine industrial trials with thermodynamic analyses [44][45][46][47][48][49][50][51][52][53][54][55]. lation"-axis, the range of the error bars corresponds to the change in thickness as the magnitudes of the contact thermal resistances are changed.…”
Section: Comparison Of Experimental Results and Numerical Simulationsmentioning
confidence: 99%
“…Based on the published papers , the industrial experimental research results with calcium treatment from 2011 to 2021 are summarized as shown in Table 1. According to Table 1, thermodynamic calculation and SEM-EDS analysis are widely used to study the formation and modification mechanism of inclusions in different steel grades, the evolution law of compositions, sizes, numbers and morphology characteristics of the different inclusions after calcium treatment in different steel grades [1][2][3]6,8,10,[12][13][14][21][22][23][24][25][26], and the optimization and improvement of calcium treatment process [4,5,9,20,29], as well as the mechanism reducing nozzle nodulation and the degree of tundish stopper erosion with calcium treatment [27,28]. The modification and local concentration of inclusions, rate-controlling step of inclusion modification and change of inclusion compositions with different reaction times in calcium treatment steel can be studied in combination with numerical simulation and kinetic models [7,11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%